2016
DOI: 10.1016/j.bbamcr.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants that mediate the sorting of human ATG9A from the endoplasmic reticulum

Abstract: ATG9A is a multispanning membrane protein required for autophagosome formation. Under basal conditions, neosynthesized ATG9A proteins travel to the Golgi apparatus and cycle between the trans-Golgi network and endosomes. In the present work, we searched for molecular determinants involved in the subcellular trafficking of human ATG9A in HeLa cells using sequential deletions and point mutations. Deletion of amino acids L(340) to L(354) resulted in the retention of ATG9A in the endoplasmic reticulum. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Even though the clearance of proteins through lysosomal degradation or cellular export might be the main function of some of these Golgi-bypassing/unconventional secretion routes, we believe that it is worth considering that the lysosomes might acquire some proportion of their resident proteins through those pathways, in normal or stress conditions. We recently found that low amounts of ATG9A, a transmembrane protein that resides in endosomes and the TGN under basal conditions [ 160 ], travels to the cell surface via a Golgi-bypassing route [ 161 ]. Moreover, when the transport of ATG9A through the Golgi stacks is prevented by mutation of a LYM motif located in its C-terminal region, the Golgi-bypassing route is sufficient to supply normal intracellular levels of ATG9A to the endosomes [ 161 ].…”
Section: New Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the clearance of proteins through lysosomal degradation or cellular export might be the main function of some of these Golgi-bypassing/unconventional secretion routes, we believe that it is worth considering that the lysosomes might acquire some proportion of their resident proteins through those pathways, in normal or stress conditions. We recently found that low amounts of ATG9A, a transmembrane protein that resides in endosomes and the TGN under basal conditions [ 160 ], travels to the cell surface via a Golgi-bypassing route [ 161 ]. Moreover, when the transport of ATG9A through the Golgi stacks is prevented by mutation of a LYM motif located in its C-terminal region, the Golgi-bypassing route is sufficient to supply normal intracellular levels of ATG9A to the endosomes [ 161 ].…”
Section: New Directionsmentioning
confidence: 99%
“…We recently found that low amounts of ATG9A, a transmembrane protein that resides in endosomes and the TGN under basal conditions [ 160 ], travels to the cell surface via a Golgi-bypassing route [ 161 ]. Moreover, when the transport of ATG9A through the Golgi stacks is prevented by mutation of a LYM motif located in its C-terminal region, the Golgi-bypassing route is sufficient to supply normal intracellular levels of ATG9A to the endosomes [ 161 ]. These observations support that the Golgi-bypassing pathway can be a very efficient way to target transmembrane proteins to endolysosomes.…”
Section: New Directionsmentioning
confidence: 99%
“…During its residence in the ER, ATG9A becomes modified by N-linked glycans on Asparagine 99, and then upon reaching the Golgi, it acquires complex, mature N-linked glycans 1 , 14 . This modification by glycosylation can be detected through western blot by the appearance of a double band 14 . Consistent with its intracellular localization, most endogenous ATG9A harbors complex N-linked glycans, and, therefore, the highermolecular weight band is predominant, with a faint lowermolecular weight band also visible (Figure 2B).…”
Section: Representative Resultsmentioning
confidence: 99%
“…The current view is that ATG2 proteins transport lipids from the ER to the cytoplasmic leaflet of the growing phagophore membrane, and ATG9A then distributes the lipids to the luminal leaflet in order to facilitate phagophore elongation [ 175 , 176 ]. ATG9A is glycosylated with a complex-type N- glycan at Asn99 between the first and second transmembrane segments; Asn99 is the only one of the potential N -glycosylation sites in ATG9A that is used [ 160 , 177 ]. The presence of ATG9A is a possible explanation for the early observations of Yamamoto and colleagues, showing that the growing edges of phagophores have binding sites for concanavalin A, wheat germ agglutinin and Ricinus communis agglutinin 120, which bind Man, Glc N Ac and sialic acid, and terminal β-Gal residues, respectively [ 178 ].…”
Section: Glycans and Autophagymentioning
confidence: 99%